Evaluation of an SMS-based mHealth intervention to enhance early infant diagnosis follow-up testing and assessment of postnatal prophylaxis - Anele Dube-Pule; Brian C. Zanoni; Cathy Connolly; Majahonkhe Shabangu; Moherndran Archary (AOSIS, 2021)
Background: Adherence to infant antiretroviral (ARV) postnatal prophylaxis and early infant diagnosis (EID) uptake is low in Africa. Promoting EID and adherence are necessary for this age group. Objectives: We evaluated an SMS-based mobile health (mHealth) intervention to enhance adherence to ARV prophylaxis and knowledge of EID and prevention of mother-to-child transmission (PMTCT) among high-risk and low-risk mother-infant pairs. Method: Two hundred and fifty-one mothers were recruited from King Edward VIII Hospital between December 2018 and October 2019. Participant information was captured, and SMS reminders were sent postnatally to promote immunisation attendance. Follow-up HIV polymerase chain reaction (PCR) test results were reviewed, and telephonic interviews were utilised for qualitative data. Results: In all, 73.3% of infants had HIV PCR tests performed at 10 weeks. This high rate could be attributed to the mHealth intervention as this is considerably higher than other national studies, though not statistically significant compared to rates reported in the district at the same time. Factors that have impacted follow-up EID rates include poor maternal knowledge of EID time points and inadequate implementation of national PMTCT protocols. High-risk mothers were younger, commenced antenatal clinic visit later, were less knowledgeable on prophylaxis and have lower-birthweight infants than lower-risk mothers. Conclusion: mHealth can play an important role in improving EID by increasing maternal knowledge. Further studies should focus on whether maternal education over an mHealth platform can increase knowledge on PMTCT and subsequently increase EID.